ISSUES FACED BY MINORITY ETHNIC GROUPS’ STUDENTS REFLECTED IN THEIR WRITING - Wiraatmaja, Triastama (Cultural Institute University of Muhammadiyah Malang, 2020)
This research attempted to determine issues faced by minority ethnic groups? students in English Language Education Department in private university in Malang, and whether ethnicity and social aspects played significant roles in the students? language proficiency reflected in their vocabulary in writing class. The researcher analysed writing samples taken from 16 students from both minority and majority ethnic groups by utilising Voyant Tools which focused on vocabulary density and average words per sentence. Followed with spreading questionnaires to eight students of minority ethnic groups and interviewing two of them who earned highest scored based on Voyant Tools. Those sessions were analysed with Thick Description to focus on related issues regarding vocabulary proficiency and ethnicities. The results taken from Voyant Tools indicated that students from minority ethnic groups were lesser than the students from majority one?s. Those results depicted the vocabulary proficiency of students from minority ethnic groups in writing, and those results were affected by educational deprived in their origins, and verbal abuse regarding their ethnicity. The researcher discovered that verbal abuse towards ethnicity regarded as individual discrimination that strengthens the majority?s idea to emphasise their superiority over the inferior. People tend to overlook the fact that verbal abuse among students was existed in universities and it affecting students? performance. This notion was supported by the result taken from Voyant Tools in which the result shown that the minority ethnic groups were lesser than majority one?s and the effect were reflected at their writing, notably their vocabulary proficiency.